2018
DOI: 10.5194/acp-18-10869-2018
|View full text |Cite
|
Sign up to set email alerts
|

Does afforestation deteriorate haze pollution in Beijing–Tianjin–Hebei (BTH), China?

Abstract: Abstract. Although aggressive emission control strategies have been implemented recently in the Beijing-TianjinHebei area (BTH), China, pervasive and persistent haze still frequently engulfs the region during wintertime. Afforestation in BTH, primarily concentrated in the Taihang and Yan Mountains, has constituted one of the controversial factors exacerbating the haze pollution due to its slowdown of the surface wind speed. We report here an increasing trend of forest cover in BTH during 2001-2013 based on lon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…Our second hypothesis is that the effect of vegetation growth on NSWS in rural areas is more profound in summer than in winter, because boreal summer (winter) has the highest (lowest) vegetation productivity. A recent study has carried out a month-long simulation using the Weather Research and Forecast model and found that the westerly or northerly wind is decelerated by 0.3-1.5 m s −1 in the western and northwestern Beijing-Tianjin-Hebei region (mostly rural areas) due to the effects of afforestation (Long et al 2018). However, they did not assess the effects of afforestation for all the seasons.…”
Section: The Seasonality Of Urbanization Impacts On the Observed Windmentioning
confidence: 99%
“…Our second hypothesis is that the effect of vegetation growth on NSWS in rural areas is more profound in summer than in winter, because boreal summer (winter) has the highest (lowest) vegetation productivity. A recent study has carried out a month-long simulation using the Weather Research and Forecast model and found that the westerly or northerly wind is decelerated by 0.3-1.5 m s −1 in the western and northwestern Beijing-Tianjin-Hebei region (mostly rural areas) due to the effects of afforestation (Long et al 2018). However, they did not assess the effects of afforestation for all the seasons.…”
Section: The Seasonality Of Urbanization Impacts On the Observed Windmentioning
confidence: 99%
“…Some studies regarding urban trees suggested that arrangement of trees led to sensible heat reduction and temperature variation [19,48]. Although trees bring positive impact to the environment, especially on the microclimate and thermal comfort, trees can also act as barriers and decrease wind speed, which ultimately will increase heat stress at a pedestrian level [37,46]. Trees also have potential to increase pollutant concentration [45].…”
Section: Treesmentioning
confidence: 99%
“…However, as the business as usual condition (i.e., without the GLP), the increased lighting demand could cause significant increase in thermal power electricity, and the associated growth of coal consumption for power generation during the past decades. This study was to assess the potential effects induced by the GLP on the severe haze pollution in the NCP (Tie et al, 2017;Long et al, 2018), and also displayed a good example to illustrate that scientific innovation can induce important benefits on environment issues. To assess the impacts of the GLP on the severe air polluted region in China, such as in the NCP, several important tools and data were used in this study, including a regional chemical/dynamical model (WRF-CHEM), satellite data (DMSP/OLS and S-NPP), and surface measurements of air pollutants.…”
Section: The Long-term Ntl Data and Coal Consumptionmentioning
confidence: 99%